Gelatin-based nanoparticles and antibiotics: a new therapeutic approach for osteomyelitis? - Sherafati Chaleshtori, Ali; Marzhoseyni, Zeynab; Saeedi, Negin; Azar Bahadori, Rosita; Mollazadeh, Samaneh; Pourghadamyari, Hossein; Sajadimoghadam, Esmaeil; Abbaszadeh‐Goudarzi, Kazem; Moradi Hasan-Abad, Amin; Sharafati Chaleshtori, Reza (Frontiers in Molecular Biosciences, 2024)
The result of infection of bone with microorganisms is osteomyelitis and septic arthritis. Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for most of its cases (more than 50%). Since MRSA is resistant to many treatments, it is accompanied by high costs and numerous complications, necessitating more effective new treatments. Recently, development of gelatin nanoparticles have attracted the attention of scientists of biomedicine to itself, and have been utilized as a delivery vehicle for antibiotics because of their biocompatibility, biodegradability, and cost-effectiveness. Promising results have been reported with gelatin modification and combinations with chemical agents. Although these findings have been suggested that gelatin has the potential to be a suitable option for continuous release of antibiotics in osteomyelitis and septic arthritis treatment, they still have not become routine in clinical practices. The most deliver antibiotic using gelatin-derived composites is vancomycin which is showed the good efficacy. To date, a number of pre-clinical studies evaluated the utility of gelatin-based composites in the management of osteomyelitis. Gelatin-based composites were found to have satisfactory performance in the control of infection, as well as the promotion of bone defect repair in chronic osteomyelitis models. This review summarized the available evidence which provides a new insight into gelatin-derived composites with controlled release of antibiotics.